The diversity of Leaf epidermal features in the genus Hyptis Jacq. (Labiatae) in West Africa (2007)
Leaf epidermal morphology of the five species of Hyptis (Labiatae) in West Africa has been studied using Light and Scanning Electron Microscopy. Epidermal cells are irregular with undulate or wavy anticlinal walls or rarely polygonal with straight to curved anticlinal walls, In H. peclimilu and H. lanceolate/, the adaxial epidermal cells are either irregular or polygonal, an observation which may be accounted for by eco-geographical differences. The periclinal walls consist of irregular ridges and cuticular folds on both abaxial and adaxial surfaces. The adaxial epidermal cells are generally larger than those on the abaxial surface. All taxa have diacytic stomata and are amphistomatic with more stomata on the abaxial surfaces. Stomata may be slightly raised, level with the surface or slightly sunken. The stomata are characterised by the presence of pronounced, overarching cuticular rims. Trichomes are multicellular or rarely unicelular, uniseriate, non-glandular or glandular, unbranched and thin walled. They are usually densely or rarely sparsely distributed on both surfaces of the leaves and are covered with numerous tubercules. Trichomes vary in size and form even on the same epidermal surface of every taxon. The glands are usually globose in shape. Some characters which are of taxonomic value include the adaxial epidermal cell shape, anticlinal wall pattern, size of stomata, epidermal cell and trichome type. A key is presented for the identification of the species.